Projeto de aproveitamento de biogás proveniente de biodigestor de rejeitos bovinos e agrícolas para geração de energia - Silva, Tony Corrêa (2024)
The intensification of milk production in the agricultural industry has a strong influence on the Brazilian economy, resulting in larger quantities of animal waste. Without prior treatment, these wastes runoff or are thrown onto crops, reaching groundwater, causing contamination problems. The biodigester system is a viable solution to this issue. In this scenario, the present study aimed to devise a method for harnessing biogas from a biodigester for the generation of electrical energy and to develop a thermodynamic modeling of biogas. The experiments were conducted at Pirapitinga Farm located in the municipality of Presidente Olegário - MG - Brazil, where a sample of biogas was collected and later analyzed at the Heat and Mass Transfer Laboratory of the Faculty of Mechanical Engineering at the Federal University of Uberlândia. The chromatographic analysis of the biogas unveiled its chemical composition: 62.86% (v/v) methane; 24.10% (v/v) carbon dioxide, 10.04% (v/v) nitrogen, 2.99% (v/v) oxygen. The biogas flow rate of 7.2 liters per second was measured using a digital anemometer. From this data, a thermodynamic modeling was developed, which consisted of an algorithm considering the polytropic process to simulate a 3-cylinder Otto engine, capable of producing 35 kW of electrical power. Using the calculated data, a motor-generator system was sized for the farm, corresponding to the domestically manufactured MWM model N229-3 engine. The high cost of the engine (estimated at R$100,000.00) and the payback period (5 years) were some of the factors that discouraged the producers at Pirapitinga Farm from investing in the energy utilization of biogas.